Hi Forum, I am trying to follow the math in Bell's original paper, and I am getting tripped up on equation (14). Does anyone know the mathematic legerdemain Bell used to go from the first equation below to the 2nd?(adsbygoogle = window.adsbygoogle || []).push({});

[itex]

\begin{align}

P(\vec{a},\vec{b})-P(\vec{a},\vec{c})=-\int{d\lambda\rho(\lambda)[A(\vec{a},\lambda)A(\vec{b},\lambda)-A(\vec{a},\lambda)A(\vec{c},\lambda)]}

\\

=\int{d\lambda\rho(\lambda)A(\vec{a},\lambda)A(\vec{b},\lambda)[A(\vec{b},\lambda)A(\vec{c},\lambda)-1]}

\end{align}

[/itex]

Here is a link to the original paper:

http://www.drchinese.com/David/Bell.pdf

I hope I am not missing something trivial, but thanks for you help!

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Question on John Bell's Original Paper

**Physics Forums | Science Articles, Homework Help, Discussion**